1978
DOI: 10.1210/jcem-47-5-1052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroid-Stimulating Hormone on Human Thyroid Carcinoma and Adjacent Normal Tissue*

Abstract: Effects of TSH on the adenylate cyclase-cAMP system and some parameters of intermediary metabolism were investigated in human thyroid carcinoma and adjacent normal thyroid tissue. Basal adenylate cyclase activity and cAMP concentrations were significantly higher in carcinomatous tissue. Basal [1-14C]glucose oxidation, 32Pi incorporation into phospholipids, and organification of iodide were similar in both tissues. Stimulation of cAMP by TSH was significantly greater in normal compared to carcinomatous tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 19 publications
1
14
1
1
Order By: Relevance
“…In cold thyroid adenoma, an intact TSH-responsive AC associated with defective iodine metabolism has been observed (De Rubertis et al 1972). In thyroid carcinoma, a marked variability from tumour to tumour was reported by Field et al (1978), despite similar morphological appearances.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In cold thyroid adenoma, an intact TSH-responsive AC associated with defective iodine metabolism has been observed (De Rubertis et al 1972). In thyroid carcinoma, a marked variability from tumour to tumour was reported by Field et al (1978), despite similar morphological appearances.…”
Section: Discussionmentioning
confidence: 93%
“…Varying degrees of impairment of iodine meta¬ bolism have been found in human differentiated thyroid carcinomas (Triantaphyllidis & Tubiana 1956;Valenta et al 1968; Lemarchand-Béraud et al 1969;Pochin 1969; Thomas (Ichikawa et al 1976;Takahashi et al 1978;Clark & Castner 1979), in TSH stimulation of adenylate cyclase (Sand et al 1976;Field et al 1978; Thomas-Morvan 1978), or in both (Carayon etal. 1978(Carayon etal.…”
mentioning
confidence: 99%
“…In thyroid carci¬ noma the response to TSH was greater than that of normal tissue (Orgiazzi, Munari, Rostagnat et al 1977;Clark et al 1981;Clark, Gerend, Goretzki & Nissenson, 1983;Clark et al 1984;Clark & Gerend, 1985), qualitatively similar to that of normal tissue (Field, Bloom, Chou et al 1978) or absent in undifferentiated thyroid carcinoma (Abe et al 1981) or in papillary carcinoma (Chang et al 1988). It is also well established that the TSH-stimulated adenylyl cyclase activity was generally lower in or absent from thyroid toxic adenoma compared with normal tissue sur¬ rounding the nodule (Tocafondi, Rotella, Tanini et al 1979;Van Sande, Mockel, Boeymans et al, 1980;Thomas et al 1984;Van Sande, Lamy, Lecocq et al 1988).…”
Section: Discussionmentioning
confidence: 97%
“…6;17;18 Initially we and others 6 did not treat subclinical hypothyroidism, in contrast to other investigators. 18 An important reason to treat subclinical hypothyroidism is to diminish the risk of thyroid adenoma and carcinoma 19;20 and in young patients to prevent growth failure and delayed development. Stem cell transplant recipients are at increased risk of developing second malignancies 21;22 An EBMT study showed thyroid cancer was the most common secondary cancer with a standardized incidence ratio (SIR) approaching 50 among long term survivors after SCT.…”
Section: Discussionmentioning
confidence: 99%